The impact of platelet-rich plasma injection on anterior cruciate ligament reconstruction: a systematic review and meta-analysis - Zhang, Yiran; Xiao, Zhikang; Fan, Zhe; Zhang, Yingxin; Xu, Jianzhong; Wang, Kun (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThis systematic review and meta-analysis evaluates platelet-rich plasma (PRP) efficacy in anterior cruciate ligament reconstruction (ACLR) through 15-year Randomized controlled trials (RCTs) data, focusing on postoperative recovery, rehabilitation acceleration, and functional outcomes optimization.MethodsWe conducted an extensive systematic search in PubMed, Embase, and Web of Science to find relevant studies on using PRP in ACLR. Randomized controlled trials analyzing the comparative effectiveness of PRP compared to control interventions in individuals undergoing ACLR were systematically identified. The focus was on studies that provided reliable outcome measures, encompassing validated clinical assessments and objective imaging results. Outcome indicators included the Visual Analog Scale (VAS) for pain perception, the International Knee Documentation Committee (IKDC) score, Lysholm score, Tegner activity scale, KT-1000 side-to-side difference, graft characteristics, and associated complications. Additionally, subgroup analyses were categorized based on evaluation timelines, distinguishing between preoperative and postoperative assessments.ResultsThis meta-analysis of 24 studies demonstrated time-dependent effects of PRP supplementation following ACLR. The PRP group exhibited significant improvement in IKDC scores at 12 months post-operatively (mean difference: 2.09, P = 0.01, I2 = 23%), while Lysholm scores showed significant enhancement at 6 months (mean difference: 3.33, P = 0.03, I2 = 58%). Pain reduction, assessed by VAS scores, was significantly greater in the PRP group at 3 months (mean difference: −1.33, P < 0.01, I2 = 38%) with borderline significance at 6 months (mean difference: −0.78, P = 0.05). Notably, PRP intervention significantly reduced anterior tibial translation compared to controls (mean difference: −1.34 mm, 95% CI: −1.56 to −1.13, P < 0.01, I2 = 73%), indicating improved knee stability. Pre-operative KT-1000 measurements suggested a trend toward reduced knee laxity in the PRP group (mean difference: −0.70 mm, 95% CI: −1.45 to 0.05, P = 0.07), though this effect did not persist post-operatively. No significant between-group differences were observed in Tegner activity scores, Signal-to-Noise Quotient, or Pivot Shift Test results at any follow-up interval.ConclusionThis meta-analysis indicates that PRP application during and shortly after ACLR offers limited clinical benefits. Although there is notable short-term pain relief, long-term efficacy remains unclear, with improvements not meeting minimal clinically important differences (MCID) and no significant changes in knee stability or graft maturation. Further research is needed to establish optimal PRP protocols and standardization for ACLR.